مجلس الإفتاء الوطني الماليزي وضوابط الفتوى فيه : دراسة وصفية نقدية - Abdul Manan bin Ismail (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2013)
This research examines the Malaysian National Fatwa Council and its regulations of the fatwa, and the discussion is through the use of the descriptive method which means describing the facts of the topic, studying the Muslim scholars' opinions and finally analyzing them to come up with reasonable and acceptable results. This study has taken into account the reality of fatwa giving process in order to document procedures and challenges of the matter. The researcher considers the references in Islamic jurisprudence and Usul Fiqh in examining judgements offered by Islamic scholars. The researcher critically studies fatwas issued by the National Fatwa Council as well as examines the fatwa process. There are also interviews with people involved in the area. The researcher studies the Malaysian National Fatwa Council in terms of control or regulation and the membership in the fatwa council as well as the qualifications of its members. The researcher concludes that the National Fatwa Council in general, follows the accepted methodology in issuing a fatwa except in some cases in which, it may not conform. The members of the fatwa council are also qualified experts, and it is proposed that members who specialize in Sharicah discuss matters relating to Sharicah only, and those who specialize in cAqidah should focus on these subjects only so that every expert offers an informed judgement when giving a fatwa.